Fleas and smaller fleas: virotherapy for parasite infections - Hyman, Paul; Atterbury, Robert J.; Barrow, Paul (Elsevier, 2013)
Bacteriophages are viruses of bacteria that are used for controlling bacterial food-borne pathogens and have been proposed for more extensive usage in infection control. Protists are now recognised to harbour viruses and virus-like particles. We propose that investigation of their prevalence in parasites be intensified. We also propose that such viruses might be considered for virotherapy to control certain parasite infections of man and animals.